Literasi Pengetahuan Masyarakat terhadap Produk Asuransi Personal Accident dan Surety Bond di PT. Bumiputera Muda 1967 Cabang Medan - Fachrunisa Winda Marpaung; Fauzi Arif Lubis (Universitas Muhammadiyah Surabaya, 2023)
Abstract In today's business world, insurance or coverage is very much needed in the business world. While the formulation of the problem in this study is how is the public's knowledge of personal accident and surety bond insurance products at PT. BUMIDA Insurance Medan Branch. The purpose of this study was to determine literacy in public knowledge about personal accident and surety bond insurance products. This research was conducted at PT. BUMIDA INSURANCE 1967 Medan Branch, which is located at Jl. Prof. H.M Yamin No. 41-V, Sidodadi, Kec. Medan Timur, Medan City, North Sumatra 20234. In this study the authors determined 2 (two) variables to be examined, namely the independent variable is a product of knowledge (X) while the dependent variable is (Y) = interest in coverage . The resulting regression equation: Y = 10.843 + 0.904X, and the coefficient of determination is 0.528. Product Knowledge is 52.8% while the remaining 47.2% is explained by other variables outside the research variables. From the t test, the t value for the Product Knowledge variable is 7.171 with a significance value of 0.000, while with a significance limit of 0.05 and in the direction of the positive regression coefficient, the t-table value is 2.013. By comparing the two values obtained, it can be seen that tcount > ttable, so that a decision can be taken to reject H0 and accept H1. The conclusion is that product knowledge partially has a significant effect on personal accident and surety bond insurance products at PT. BUMIDA Medan Branch.Keywords: Knowledge of Products, Personal Accident, Surety Bond